Plant-Based Milks: Hemp - Sarah Curl; Daniela Rivero-Mendoza; Wendy J. Dahl (EDIS, 2020)
Hemp milk is a plant-based milk growing in popularity. Commercial hemp seed, used in the production of hemp milk, contains only trace amounts of the compound tetrahydrocannabinol (THC), much too low to produce any psychoactive effects from consuming the milk. This new 4-page publication describes the composition of hemp milk and the potential health benefits and risks. Written by Sarah Curl, Daniela Rivero-Mendoza, and Wendy J. Dahl, and published by the UF/IFAS Food Science and Human Nutrition Department. https://edis.ifas.ufl.edu/fs420